Climate trouble women in coastal communities in the Philippines respond to climate changes - Dalisay, Soledad Natalia M. (2018)
Access online through this link: https://journals.upd.edu.ph/index.php/DILIMANGENDERREVIEW/article/view/6590/5733
Keywords: Climate change; Coastal community